Problematika Keputusan Tata Usaha Negara Yang Bersifat Fiktif Positif Setelah Undang-Undang Nomor 11 Tahun 2020 - Abrianto, Bagus Oktafian; Nugraha, Xavier; Hartono, Julienna; Kosuma, Indah Permatasari (Arena Hukum, 2023)
This doctrinal research aims to analyze the development of legal consequences and legal protection related to the Government's omission on applications to state administrative officials. Until the enactment of the Job Creation Act, there were 3 (three) different legal norms regarding the legal consequences of the Government's omission on applications to state administrative officials, namely fictitious rejection, in the State Administrative Court Law, fictitious approval followed up with applications, in the Government Administration Act, and fictitious approval without being followed up with an application, in the Job Creation Act. Based on the principle that the new law overrides the old law, the applicable legal consequences are as regulated in the Job Creation Act. Then, legal protection related to the Government's omission on applications to state administrative officials are the imposition of administrative sanctions, submitting applications for the determination of fictitious approval of state administrative decisions to the Administrative Court, filing claims based on government actions disputes, or submitting reports to the Ombudsman.